Iran's Hypersonic Missile Attack on Israel and Its Impact on Geopolitics and Oil Prices - SULISTYAWATI, Laeny; HANGGARINI, Peni (Indonesia Strategic Sustainability, 2024)
Purpose:This paper explores Iran's missile attacks on Israel in April 2024 and October 2024 that have had an impact on the Middle East. On October 1, 2024, more than 180 ballistic missiles were fired into the skies of Israel. Iran officially admitted firing hypersonic missiles into Israel in retaliation for Israel's campaign against Iran's ally Hezbollah in Lebanon.Methodology:The research method used in this paper is qualitative descriptive-analytical. Qualitative method: Data is collected from literature studies in the form of books, articles, news, internet-based studies, digital books, previous research, journals and other relevant sources and previous research.Findings:The conflict between Iran and Israel has been going on for a long time, since the Islamic revolution in 1979. The conflict between the two countries has heated up again due to ballistic, cruise, and hypersonic missile attacks on Israel. Iran's attacks have angered Israel because they caused damage in 10 locations. Iran's latest sophisticated missile attacks, such as hypersonics, have damaged Israel and caused losses of Rp827 billion.Implication:International relations regarding geopolitics and complex interdependence. Practically, the results of this study provide insight for stakeholders of countries in the Middle East in formulating more comprehensive policies to respond to changing dynamics in the region.